Exploring The Influence of Microlearning Content and Mobile-Assisted Language Learning (MALL) Platforms on English Language Proficiency - Herlangga, Ogie Yudha; Sukarno (PT FORMOSA CENDEKIA GLOBAL, 2024)
This quantitative study examines the influence of Microlearning Content and Mobile-Assisted Language Learning (MALL) Platform on English proficiency among participants in the Ministry of Information and Communications (Bakti Kominfo) English for Tourism Program. Drawing upon a comprehensive review of literature, the research elucidates the evolving landscape of language education, emphasizing the emergence of innovative methodologies such as microlearning and MALL. Through regression coefficient analysis, the study empirically demonstrates the individual influences of Microlearning Content and MALL Platform on English proficiency. Results indicate that Microlearning Content significantly influences English proficiency, with a relative contribution of 46.3%. Similarly, MALL Platform exhibits a substantial impact on English proficiency, contributing 43.0% to language learning outcomes. Furthermore, the combined influence of Microlearning Content and MALL Platform was found to significantly affect English proficiency, contributing to 55.2% of language proficiency variation. These findings underscore the importance of integrating technology-enhanced learning approaches to foster English language proficiency in non-formal education settings. The research offers insights for educators, policymakers, and practitioners to design effective language programs that leverage microlearning and MALL platforms to meet the evolving needs of language learners in the digital age